ESTIMATING THE MONETARY POLICY REACTION FUNCTION IN IRAQ: AN EMPIRICAL ANALYSIS - Lecturer Dr. Helmy Ibraheem Menshad (Scholars Digest Publishing, 2023)
The main aim of this paper is to estimate the monetary policy reaction function in Iraq for quarterly data for period (2005-2021) using the Generalized method of moments (GMM) in order to determine the extent to which monetary policy responds through interest rate movements to changes in the inflation rate and output gap. The main results of the research were the high level of inertia in monetary policy and the weak response in interest rate movements to combat inflationary pressures and address deviations of the actual output from potential output.
Keywords: Monetary policy reaction function, Taylor rule, Monetary policy, Generalized Method of Moments (GMM), Interest rate smoothing.